Role of the cation formal charge in cation–π interaction. A survey involving the [2.2.2]paracyclophane host from relativistic DFT calculations. (26th October 2015) - Ortolan, Alexandre O.; Caramori, Giovanni F.; Frenking, Gernot; Muñoz-Castro, Alvaro
Abstract : Of charge and cations. Isoelectronic cation–π complexes unravel the nature of variation of the interaction. Abstract : The role of the metal formal charge in the cation–π interactions has been evaluated with relativistic DFT methods involving a versatile π-cryptating structure, namely [2.2.2]paracyclophane. Our study focuses on experimentally characterized [([2.2.2]pCp)M] n + systems with M = Ag + and Sn 2+ and their Cd 2+ and In + counterparts, which exhibit 5s 0 5p 0 and 5s 2 5p 0 electron configurations. The acceptor capabilities increase when the metal charges go from 1+ to 2+, resulting in a large stabilization of the interaction. For the studied 5s 0 5p 0 cations Ag + and Cd 2+, the most stable conformation namely [(η 2 :η 2 :η 2 -[2.2.2]pCp)M] n +, the electrostatic contribution is more favorable by −9.3 kcal mol −1, whereas the Δ E Orb contribution increases by −151.6 kcal mol −1 towards a more favourable situation in the 2+ counterpart. Similarly in the 5s 2 5p 0 cationic group, the isoelectronic Sn 2+ and In + systems depict variation of the electrostatic and orbital terms, with a considerable decrease of the stabilizing Δ E Orb contribution, and in a lesser amount the Δ E Elstat term. Thus, the variation of the interaction energy between the M + and M 2+ isoelectronic counterparts can be ascribed mainly to the variation of the Δ E Orb term, leading to a more covalent character of the interaction retaining a similar bonding scheme.